Set in motion by data: Human and data intra-actions in educational governance. Issue 2 (4th March 2023) - Madsen, Miriam
ABSTRACT: With the increased use of data in the governance of education, studies on how human beings interact with data become increasingly important. Recent scholarship has conceptualized human responses to data through the notion of affectivity. While this conceptualization offers a viable alternative to previous rational choice theorizations of human responses to data that over-emphasize rational though, it in turn under-emphasizes rational thought. This paper theorizes human responses to data as a matter of being set in motion by data, a term that includes rational thought, affect, and other responses. Through the philosophy of agential realism and an empirical analysis of various actors engaging with Danish graduate unemployment data, the paper elaborates how data and human beings (among other entities) intra-act and how human beings are affected by data, both in terms of what the data articulate and in terms of a code of conduct for dealing with data.